Analysis of the Influence of Load Transmission Error on the Vibration Characteristic of Spiral Bevel Gear based on MASTA Simulation - Yu You; Xuemei Cao (Jixie chuandong)
In order to improve the smoothness of the spiral bevel gear transmission system， the changing law of gear vibration characteristics under different load transmission errors is studied， the finite element model of the spiral bevel gear transmission system is established with the MASTA software as a tool， and the result is obtained by changing the load different load-bearing transmission errors. Taking the vibration acceleration waterfall diagram， vibration acceleration amplitude spectrum and noise curve diagram as objects， the gear vibration characteristics under different loads are compared and analyzed. The results show that， the vibration and noise of the gear will tend to decrease when the load transmission error fluctuation decreases. The analysis results provide a reliable basis for improving the stability of the gear transmission system.